DEVELOPMENT OF CEFR-BASED QOWA'ID LEARNING EVALUATION TOOL WITH THE HELP OF WORDWALL INTERACTIVE GAMESTO IDENTIFY STUDENTS' UNDERSTANDING - Irfan Hania; R. Umi Baroroh; Madah Rahmatan; Alimudin; Yuli Imawan (ALSINATUNA, 2022)
This development research aims to develop a CEFR-based qowa'id learning evaluation tool using an interactive Wordwall game with the aim of identifying the level of student understanding and so that it can be accessed by students more flexibly without being limited by space and time, more effectively and is also expected to be more efficient in learning. its maintenance. This research is a research and development (Research & Development). This research aims to produce a product or develop a product. The results in this study are based on the student's own assessment response described through the distribution of a questionnaire that has been carried out with a percentage score of 91.19% of the maximum score of 100%. Student test results to identify qowa'id understanding, at the level of understanding the material at 78.51% and not understanding the material at 21.49%. Therefore, it can be concluded that almost all students give an assessment that can be categorized as Very Good on the Wordwall interactive quiz game that has been used and from the test results that have been carried out that on average students understand the qowa'id material that has been combined with the interactive Wordwall game.